Is There Justice in Violent Family-Related Crimes? How Femicide has Crossed the ocean: meanings and ages between “The Oresteia” by Aeschylus and “The Glass Bottle Trick” by Nalo Hopkinson - Quiangala, Anne (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
“The Oresteia” is a historical landmark in the fine arts, such as theatre and literature, due to its aesthetic and political elements that continue to impact contemporary life, particularly in the realm of family-related crimes. Therefore, it is relevant to analyze the permanence of that phenomenon with a critical lens. Since their relevance today is as a kind of representation of social antagonism, which continues, it results in demands for typing as a specific crime: femicide. Considering that, we contextualize these themes in the Feminist Literary tradition to comprehend how a Black female Caribbean experience can complicate the discussion about gendered and racialized violence. Contrasting the Greek classic with a contemporary short story entitled “The Glass Bottle Trick” by Nalo Hopkinson through a Black female feminist perspective, it is possible to observe some intertextual elements that connect the “social curses” experienced by Clytemnestra, and likewise the Heroine Beatrice. In both of these texts, the presence of Erinyes (The Furies) influences the discussion about retributive justice and countercolonial conscience.